Accounting Analysis of Cost and Benefit of Celebrity Endorsements in Micro, Small and Medium Enterprises - Priyadi, Ira Hasti; Halida, Uly Mabruroh; Jannah, Safiratul; Rohmaniyah, Alfiatur (Institut Agama Islam Negeri (IAIN) Madura, 2024)
Indonesian. Abstract describes the purpose of research writing, methodology, and shows the In the era of digitalization, social media has become an integral part of human life, not only as a communication tool but also as a branding and marketing platform. This phenomenon creates opportunities for businesses to use celebrities, well-known individuals on social media, as product promotion agents. However, this strategy is not without significant costs. This research aims to conduct a cost-benefit analysis (CBA) on product promotion through celebrity endorsements in Indonesia, with a focus on MSMEs in Pamekasan. Mixed research methods are used to combine quantitative and qualitative approaches. Data was obtained through interviews with MSME actors and program celebrities, documentation and literature studies. Quantitative data includes endorsement rates for well-known celebrities, while qualitative data involves evaluating the benefits received by MSMEs. It is known that celebgrams charge varying rates, with some of the most expensive celebgrams reaching IDR 50,000,000. A cost-benefit analysis was conducted to assess the efficiency of investment in this promotion. It can be seen that several MSMEs achieved the highest Cost-Benefit Ratio (CBR), indicating high efficiency in generating benefits.